Uji Validitas dan Praktikalitas Website Eduautism untuk Orang Tua dengan Anak Gangguan Spektrum Autisme: Indonesia - Rahmita Juliandori; Johandri Taufan; Rahmahtrisilvia Rahmahtrisilvia; Endang Sri Handayani (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the validity and practicality test results that have been conducted regarding the EduAutism website. The method used in this study is the Research and Development method, guided by the Borg & Gall development model, which has been modified into 6 steps. The data collection technique uses a Likert scale questionnaire. Data analysis uses a quantitative approach. The data analysis technique is carried out quantitatively using the Likert scale, where the scores obtained are calculated and converted into percentages to determine the feasibility category. The results of this study include the website validity assessed by experts, with a final score averaging 81.3% in the very feasible category. Meanwhile, the practicality test conducted with parents of children with autism residing in Padang City obtained an average final result of 88.3% in the very feasible category. The implication of this research for the public is the availability of a validated one-stop digital information access to empower parents in performing appropriate early interventions and facilitate the community in accessing autism directory services in Padang City. Further research is recommended to test the effectiveness of the EduAutism website on a larger sample and to develop more comprehensive features, such as education, health services, and interactive forums, in order to enhance its usefulness for parents of children with Autism Spectrum Disorder.